Profil Kebugaran Kardiorespirasi pada Pra-Lansia di Desa Jatisari - Aprilianti Anggaraini (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Cardiorespiratory fitness reflects the ability of the heart and lungs to efficiently circulate oxygen-containing blood to meet the metabolic demands of the muscles during exercise during sports activities. Decreased cardiorespiratory function can increase the risk of death from heart disease. Therefore, proper cardiorespiratory fitness is needed to reduce the risk of death. This research uses quantitative research methods with observational techniques because it is accurate in collecting data. The results of a study conducted on October 14 2022 showed that the level of cardiorespiratory fitness in Jatisari village was at a good level, which at the age of 55-60 years still had good cardiorespiratory fitness as evidenced by the good results of the Six Minute Walking Test. This is because the majority of Jatisari village residents have good physical activity so that their cardiorespiratory fitness is still maintained. Based on the results and discussion that has been done, it is hoped that this research can be used as a reference for other studies related to cardiorespiratory fitness of pre-elderly in other areas as well as other related research in Jatisari village.